Neotypification, distribution, and conservation status of Austrocylindropuntia cylindrica (Cactaceae) - Loaiza S., Christian R. (Phytotaxa, 2023)
Austrocylindropuntia cylindrica (Cactaceae) is neotypified based on a specimen preserved at ASU (isoneotype at DES) collected in the northern Andean region of Ecuador. The few details reported in the original description and its historical and current distribution suggest that the species was most likely originally collected from Ecuador rather than Peru. Additionally, an updated map of the distribution of A. cylindrica in the Andean region is presented.